“Inclusión de harina de banano (Musa paradisiaca) en la dieta sobre los parámetros productivos y la calidad de la carne (Oreochromis Spp)” - Moposita Vistin, David Sebastián (2021)
In the current decades the tilapia (Oreochromis Spp) has been introduced in all countries susceptible to cultivate it, it is the fourth most cultivated species worldwide, adaptable to different environments, food and water quality, being important in aquaculture in intensive system with rapid growth and excellent yield. In this sense, the objective of the research was to determine the inclusion of banana flour (Musa paradisiaca) in the diet on the productive parameters, as an alternative by-product in the fattening of tilapia (O. spp). The treatments evaluated are made up of supplementation with banana flour (0, 10, 15, 20%), in the fattening stage in experimental units, product of the 4 treatments and 4 repetitions. 16 cages were developed and randomly distributed, 128 tilapias were introduced to the research site that was distributed for each treatment and repetitions. It became a DCA was used and Tukey (p<0.05) was used to compare the means. The results obtained in the research the T1 treatment including banana flour at 10% presented better yields in weight gain obtaining a 15.7 gr, the consumption of food was palatable with what led to the tilapia consuming more quantity, the food conversion at the beginning was 28.99% and ending with 44.47%, having as a benefit a low mortality in the consumption of this by-product, with a total growth in height of 5.52 cm, according to the proximal analysis of the study of bananas was suitable providing an extra nutritional assessment in the diet, it is considered that in the result of the yield of the fillet and the yield to the carcass was 39.29%, 93.6% , obtaining a lower value in the by-products of 60.61%. It was concluded that among the four treatments the most acceptable is the 10%, which determined that when replaced with by-products of plant origin would not affect the biological parameters and yield of the meat. Keywords: Inclusión, by-product, diet, intensive, supplementation, analysis